Entre o visível e o invisível : a morte como estratégia de legitimação do poder régio da primeira dinastia portuguesa - Santos, Airles Almeida dos (2019)
The first Portuguese Dynasty - Afonsina or Burgundy - is characterized by the warrior and reconquering personality of its kings as well as by the performance of these monarchs in the legal area. The period between the reigns of D. Dinis and D. Fernando was marked by the perfection of the judicial system, the official characterization of Portuguese as the language of the kingdom, the promotion of the arts and knowledge with the creation of the first university and the signing of the Treaty of Alcanizes (1279 ) that established the border with Castile. It was also a time of endless wars against the Castilian monarchy and other European kingdoms, plague epidemics and the dynastic crisis of 1383-85 that led to the enthronement of a new dynasty, Avis. The events that followed after the death of Don Fernando reveal a disturbance in the idea of continuity of power and the year 1383 definitively marks the end of the Afonsina Era. In this master's degree research in History, our purpose is to demonstrate how the phenomenon of death is inserted in the relations of power in the Low Portuguese Middle Ages. By means of the analysis of the wills produced by the king D. Dinis (government from 1279 to 1325), Afonso IV (from 1325 to 1357), Pedro I (from 1357 to 1367) and D. Fernando (from 1367 to 1383) we have had as objective in our research to examine how the elaboration of the image of death, the cult of these illustrious dead, the manifestations and funeral symbols represent the symbolic struggles for the permanence of the authority and the regal power, that is, as the manipulation of death appears as a strong element for the perpetuation of the power of the monarchs of the First Dynasty in Portugal. Thus, between bodies and graves, between the visible and the invisible, the funeral ritual served to legitimize the role of kings, head of the kingdom, before the rest of society. If the pluralist type of power was a feature of policy in the Middle Ages, the symbolic and ideological legitimization of the search for power was a constant effort of the monarchy. The structure of symbolic legitimation was always used as a way to consolidate the role of these monarchs as occupants of a prominent place in medieval Lusitanian society: real power imposes itself symbolically and through death we will show how this happens.